Neutrophil Function in an Inflammatory Milieu of Rheumatoid Arthritis - Weiqian Chen; Qin Wang; Yini Ke; Jin Lin (Journal of Immunology Research)
Rheumatoid arthritis (RA) is an inflammatory autoimmune disease characterized by the presence of autoantibodies against citrullinated protein antigens and proinflammatory cytokines which cause chronic synovitis, bone erosion, and eventual deformity; however, the precise etiology of RA is unclear. In the early stage of RA, neutrophils migrate into the articular cavity, become activated, and exert their function in an inflammatory process, suggesting an essential role of neutrophils in the initial events contributing to the pathogenesis of RA. Solid evidence exists that supports the contribution of neutrophil extracellular traps (NETs) to the production of autoantibodies against citrullinated proteins which can trigger the immune reaction in RA. Concurrently, proinflammatory cytokines regulate the neutrophil migration, apoptosis, and NET formation. As a result, the inflammatory neutrophils produce more cytokines and influence other immune cells thereby perpetuating the inflammatory condition in RA. In this review, we summarize the advances made in improving our understanding of neutrophil migration, apoptosis, and NET formation in the presence of an RA inflammatory milieu. We will also discuss the most recent strategies in modulating the inflammatory microenvironment that have an impact on neutrophil function which may provide alternative novel therapies for RA.